Development of 7 GHz bowtie shaped substrate integrated waveguide bandpass filter with emphasis on inter-resonator coupling - Rehman, M.Z.U. (Institute of Electrical and Electronics Engineers Inc., 2017)
Modern communication systems are required to be compact in size; hence devices building up the system face the challenge to be miniaturized. An iterative designed Bowtie shaped two pole planar bandpass filters utilizing triangular substrate integrated waveguide (SIW) resonators are presented. The triangular cavity design structure is presented; and the coupling of two cavities forms the first iteration of the bowtie shaped filter. The second iteration with reduced interresonator coupling area is also designed, simulated and fabricated for the center frequency of 7 GHz. The bandpass filter maintains high quality factor. The filter's responses reveal that along with miniaturization a better performance in terms of filter's insertion loss being better than 0.2 dB and return loss presented to be less than 30 dB is achieved. © 2016 IEEE.